2008
DOI: 10.1103/physrevlett.100.191601
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Bound and Causality Violation

Abstract: In recent work we showed that, for a class of conformal field theories (CFT) with Gauss-Bonnet gravity dual, the shear viscosity to entropy density ratio, eta/s, could violate the conjectured Kovtun-Starinets-Son viscosity bound, eta/s > or = 1/4 pi. In this Letter we argue, in the context of the same model, that tuning eta/s below (16/25)(1/4 pi) induces microcausality violation in the CFT, rendering the theory inconsistent. This is a concrete example in which inconsistency of a theory and a lower bound on vi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

31
577
2
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 445 publications
(612 citation statements)
references
References 37 publications
(48 reference statements)
31
577
2
2
Order By: Relevance
“…This scale does not show up in our calculations because we have considered perturbations of maximally symmetric backgrounds where the perturbation operator (2.7) is simply a constant multiple of the Einstein perturbation operator. This is no longer the case when the background has a non-trivial Weyl tensor, as in the case of the planar black hole calculation of [39].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This scale does not show up in our calculations because we have considered perturbations of maximally symmetric backgrounds where the perturbation operator (2.7) is simply a constant multiple of the Einstein perturbation operator. This is no longer the case when the background has a non-trivial Weyl tensor, as in the case of the planar black hole calculation of [39].…”
Section: Discussionmentioning
confidence: 99%
“…A third pathology was recently identified on the Einstein branch, through calculations of the viscosity-entropy bound [39] for gauge theories with a Gauss-Bonnet gravity dual. In the background of an EGB planar black hole, it was found that graviton wave packets can propagate with superluminal speeds whenever 9 25 ≤ 8αk 2 ≤ 1, where 1/k is the AdS length.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of Lovelock theory, this case has received attention since it's the simplest case that admits a unique constant curvature solution that also propagates a graviton [47][48][49]. The theory therefore reads 5) and the black holes solution reduces to…”
Section: Pure Quasi-topological Gravitymentioning
confidence: 99%
“…KSS bound [3] (see [4] and [5]). Lovelock theories provide one with a setup where certain control at a computational level can be attained.…”
Section: Jhep04(2017)066mentioning
confidence: 99%
“…Only with the higher derivative corrections [71][72][73] or in a anisotropic gravity background [74][75][76][77] one can get deviation from 1 4π . In order to introduce temperature dependence behavior of η/s, we will follow the formalism in [78][79][80] and continue our studies in [65].…”
Section: Jhep06(2015)046mentioning
confidence: 99%